1986
DOI: 10.1002/pc.750070107
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission during irreversible deformation in short fiber reinforced poly(vinyl chloride) composites

Abstract: Acoustic emission (AE) during irreversible deformation in short glass fiber reinforced poly(viny1 chloride] (PVC) composites was studied using a piezoelectric crystal transducer. Compared to the well-coupled composites, many more AE events were observed during tensile deformation in the poorly-coupled composites, presumably due to failure at the fiber-matrix interface. No fiber fracture was detected in the tensile tests for either well-coupIed or poorly-coupled composites. Irreversibility of acoustic emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Pioneered by Kaiser,16) acoustic emission AE has been a common tool in investigating damage processes in a wide variety of materials including metals 17,18) and composites. 5,19) From the tables reported in Faudree et al Figure 8(a) shows AE events during the tensile tests in the low amplitude (25-60 dB) range, which have been correlated with small-scale damage such as microcracking and fiber end debonding. 5,13,19) For example, fiber reinforced composites used in dentistry under flexural loading emitted low amplitude AE 25-60 dB events corresponding to polymer matrix cracking, 19) while Yuan et al reported E-glass reinforced PVC undergoing tension emitted AE in the same range, between about 25-60 dB corresponding to fiber-matrix debonding.…”
Section: Volume Fraction and Fiber End Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pioneered by Kaiser,16) acoustic emission AE has been a common tool in investigating damage processes in a wide variety of materials including metals 17,18) and composites. 5,19) From the tables reported in Faudree et al Figure 8(a) shows AE events during the tensile tests in the low amplitude (25-60 dB) range, which have been correlated with small-scale damage such as microcracking and fiber end debonding. 5,13,19) For example, fiber reinforced composites used in dentistry under flexural loading emitted low amplitude AE 25-60 dB events corresponding to polymer matrix cracking, 19) while Yuan et al reported E-glass reinforced PVC undergoing tension emitted AE in the same range, between about 25-60 dB corresponding to fiber-matrix debonding.…”
Section: Volume Fraction and Fiber End Effectsmentioning
confidence: 99%
“…[3][4][5][6] Tyson and Davies found by photoelastic experiments that interfacial shear stresses were higher than theories predict, most notably at the fiber ends.…”
Section: Volume Fraction and Fiber End Effectsmentioning
confidence: 99%
See 3 more Smart Citations